Improved MPPT controls for a standalone PV/wind/battery hybrid energy system - Otmane Zebraoui; Mostafa Bouzi (Institute of Advanced Engineering and Science, 2020)
In this paper, we present the modeling, optimization and control of a standalone hybrid energy system combining the photovoltaic and wind renewable energy sources to supply a dc electrical load, with storage batteries as a backup source. With the aim of improving the energy performance of the proposed system, we developed an MPPT controller based on new hybrid and robust approaches to evolve the power quality produced by both PV and Wind subsystems. For the PV subsystem, the proposed approach is based on the methods perturb and observe (P&O), sliding mode control (SMC) and fuzzy logic control (FLC). For the Wind subsystem, the proposed technique is based on the hill climbing search algorithm (HCS) and the fuzzy logic control. Also, to evaluate the efficiency of the developed controls and to analyze the behavior of each system during their maximum power point tracking, a comparison study was carried out with conventional techniques and the simulations are performed under varying weather conditions. The simulations results show the good performance of the proposed MPPT controls compared to other methods with better response time, a higher optimal power point and negligible oscillations.